Growth and Success Rate of Mangrove Rehabilitation Activities in Moti Island, Moti District, Ternate City - Abubakar, Salim; Rina, Rina; Kadir, Masykhur Abdul; Subur, Riyadi; Sunarti, Sunarti; Abubakar, Yuyun; Susanto, Adi Noman; Asrining Pertiwi, Reni Tyas; Ahmad, Aditiyawan; Hi. Kader, Iwan (Agrikan Jurnal Agribisnis Perikanan, 2021)
This research was carried out on Moti Island, Moti District, Ternate City, North Maluku Province for 6 months, April - September 2021. This study used mixed research methods between quantitative and qualitative research with the aim of complementing the description of the study results regarding the phenomenon being studied and to strengthen research analysis. Data collection consisted of interviews, questionnaires and field observations. The assessment of plant success was carried out through a sampling technique using the Systematic Sampling with Random Start method, ie the first plots were made randomly and the next plots were made systematically. The results showed that the plant height growth (Growth rate) in Tafaga Village in an area of 100 x 100 meters with an average of 31 cm. While the area is 100 x 50 meters with an average of 49 cm. Meanwhile, in Figur Village, the general population experienced good growth with an average of 63 cm. The success of rehabilitation activities in Tafaga Village was very low at 9% and 21% so that they were not successful overall. While in Figur Village it is considered successful with 80% success.